2008
DOI: 10.1007/s10384-008-0580-4
|View full text |Cite
|
Sign up to set email alerts
|

Current status of anti-vascular endothelial growth factor therapy in Europe

Abstract: Vascular endothelial growth factor (VEGF) is an important modulator of angiogenesis, and has been implicated in the pathology of a number of conditions, including age-related macular degeneration (AMD), diabetic retinopathy, and cancer. AMD is a progressive disease of the macula and the third major cause of blindness worldwide. If not treated appropriately, AMD can progress rapidly, causing legal blindness within months of the second eye becoming affected. Until recently, the treatment options for AMD have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 28 publications
0
20
1
2
Order By: Relevance
“…The mammalian VEGF family presently contains five members: VEGF-A, placenta growth factor (PlGF), VEGF-B, VEGF-C, and VEGF-D. VEGF-A has important roles in mammalian vascular development and in diseases involving abnormal growth of blood vessels. Recent clinical studies have demonstrated the significance of VEGF-A in ocular neovascularization (e.g., diabetic retinopathy and aged-macular degeneration) with use of VEGF-A neutralizing antibodies [9]. VEGF-C and VEGF-D are main lymphangiogenic factors in both physiological and pathological conditions.…”
Section: Vegf/vegfr System In Lymphangiogenesismentioning
confidence: 99%
“…The mammalian VEGF family presently contains five members: VEGF-A, placenta growth factor (PlGF), VEGF-B, VEGF-C, and VEGF-D. VEGF-A has important roles in mammalian vascular development and in diseases involving abnormal growth of blood vessels. Recent clinical studies have demonstrated the significance of VEGF-A in ocular neovascularization (e.g., diabetic retinopathy and aged-macular degeneration) with use of VEGF-A neutralizing antibodies [9]. VEGF-C and VEGF-D are main lymphangiogenic factors in both physiological and pathological conditions.…”
Section: Vegf/vegfr System In Lymphangiogenesismentioning
confidence: 99%
“…New vessels cause edema, hemorrhages, and exudates due to the ability of VEGF to increase vascular permeability [8,9]. Application of anti-VEGF agents showed con-vincing results in studies aimed at delaying CNV development in human subjects [14]. Pigment epithelium-derived factor (PEDF), the most potent inhibitor of angiogenesis [15], serves as an antagonist of VEGF and the balance of these two factors regulates angiogenesis in retina [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 10 years, a number of new antibodies against VEGF-A emerged for intraocular treatment. These include pegaptanib (Macugen; Eyetech Pharmaceuticals Inc., New York, N.Y., USA), ranibizumab (Lucentis, Novartis Pharma, Basel, Switzerland) and bevacizumab (Avastin, Novartis Pharma) which are widely used as intravitreal injection (IVT) therapy for neovascular AMD [3,4,5]. …”
Section: Introductionmentioning
confidence: 99%